The peoples of Southeast Asia today : - Robert L. Winzeler (AltaMira Press, 2011)
The Peoples of Southeast Asia Today offers an anthropological treatment of the ethnography and ethnology of Southeast Asia, covering both the mainland and the insular regions. Based on the proposition that Southeast Asia is a true culture area, the book offers background information on geography, languages, prehistory, and history, with a particular emphasis on the role of colonialism and the development of ethnic pluralism. It then turns to classic anthropological topics of interest, including modes of adaptation, ways of life, and religion, all illustrated with relevant, current case studies. Students will find well-supported discussions of subjects ranging from the development of agriculture and language dispersals, to fantasy and reality in hunter-gatherer studies, to disputed interpretations of Thai Buddhism and Javanese Islam, to ongoing government efforts to manage religion, create proper citizens, resettle and assimilate indigenous populations, end shifting cultivation, and promote modernization.